Protective activity of Tinospora cordifolia (Willd.) Hook. f. and Thoms. and Withania somnifera (L.) Dunal against lipid peroxidation, protein oxidation and deoxyribose oxidation: Wijesekara M.A.,1* Soysa P.,1 Jayasena, S.,1 Kottahachchi D.U.,2 Perera D.,3 Jayasiri A.P.A.,4 Wimalachandra M.1 and Gooneratne L.V.1 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2023)
Withania somnifera L. (family - Solanaceae) and Tinospora cordifolia (family - Menispermaceae), medicinal herbs have different biological properties such as anticancer, immunomodulatory, hypoglycemic, anti-hepatotoxic, anti-inflammatory, gastroprotective, antioxidant, radioprotective effects. The present study was carried out to evaluate the protective effects of aqueous extracts of T. cordifolia (TC) and W. somnifera (WS) against lipid peroxidation, protein oxidation, and deoxyribose oxidation. The potential of inhibition of lipid peroxidation, protein oxidation, and deoxyribose oxidation by different concentrations of TC and WS aqueous extracts was tested with standard protocols. The EC50 values for inhibition of lipid peroxidation of T. cordifolia (TC) and W. somnifera (WS) were 146.2±1.2 ug/mL and 37.1±1.6 ug/mL, respectively. The EC50 value obtained for ascorbic acid as a positive control was 47.1±.1.1 ug/mL. Both extracts of TC (EC50 8.0±1.4 ug/mL) and WS (EC50 7.2±1.1 ug/mL) showed higher protective activities against the inhibition of deoxyribose oxidation compared with the positive control Gallic acid (EC50 8.6±1.0 ug/mL). W somnifera (EC50 75.5±1.0 ug/mL) and T. cordifolia (EC50 112.4±1.7 ug/mL) showed less potential for inhibition of protein oxidation compared to positive control ascorbic acid, which was EC50 57.0±1.3 ug/mL. The potential for inhibition of protein oxidation of both WS (EC50 75.5±1.0 ug/mL) and TC (EC50 112.4±1.7 ug/mL) was less than the positive control ascorbic acid (EC50 57.0±1.3 ug/mL). W somnifera exhibited a more potent protective activity against lipid peroxidation, protein oxidation, and deoxyribose oxidation than TC. TC showed moderate activity compared with positive controls. Hence WS and TC may serve as potential sources of natural antioxidants for pharmaceutical applications.